2023
DOI: 10.1146/annurev-nutr-061021-030404
|View full text |Cite
|
Sign up to set email alerts
|

Iron Homeostasis During Pregnancy: Maternal, Placental, and Fetal Regulatory Mechanisms

Abstract: Pregnancy entails a large negative balance of iron, an essential micronutrient. During pregnancy, iron requirements increase substantially to support both maternal red blood cell expansion and the development of the placenta and fetus. As insufficient iron has long been linked to adverse pregnancy outcomes, universal iron supplementation is common practice before and during pregnancy. However, in high-resource countries with iron fortification of staple foods and increased red meat consumption, the effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 145 publications
1
9
0
Order By: Relevance
“…However, in vitro studies have indicated that EPO does not inhibit the release of ferritin from hepatocytes [ 3 ], implying the existence of an intermediary EPO reactive ferritin inhibitor. The transcript Fam132b, which has been renamed Erfe, is induced and maintains high expression for 24–48 h just before ferritin inhibition, consistent with the evidence that erythropoietic activity affects ferritin expression [ [4] , [5] , [6] , [7] ]. While erythroferrone protein has been previously been categorized as C1q/tumor necrosis factor (TNF)-related protein 15 (CTRP15) and myonectin [ 8 ], its novel primary function in controlling ferritin and iron homeostasis is noteworthy.…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…However, in vitro studies have indicated that EPO does not inhibit the release of ferritin from hepatocytes [ 3 ], implying the existence of an intermediary EPO reactive ferritin inhibitor. The transcript Fam132b, which has been renamed Erfe, is induced and maintains high expression for 24–48 h just before ferritin inhibition, consistent with the evidence that erythropoietic activity affects ferritin expression [ [4] , [5] , [6] , [7] ]. While erythroferrone protein has been previously been categorized as C1q/tumor necrosis factor (TNF)-related protein 15 (CTRP15) and myonectin [ 8 ], its novel primary function in controlling ferritin and iron homeostasis is noteworthy.…”
Section: Introductionsupporting
confidence: 69%
“…Having previously been categorized as C1q/TNF-related protein 15 (CTRP15), and myonectin [ 8 ], erythroferrone (ERFE), and Family32b before renaming [ [4] , [5] , [6] , [7] ], a significant role in regulating ferritin and iron homeostasis has recently been demonstrated. Many recent studies have clarified its relationship with atherosclerosis, myocardial fibrosis, insulin resistance, ulcerative colitis, and dyslipidemia [ [22] , [23] , [24] , [25] , [26] , [27] , [28] ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the observed variations in iron-related parameters across trimesters could be attributed to the remarkable physiological demand for iron during pregnancy [ 15 ]. The escalating iron requirement is intricately linked to gestational age, surging from 0.8 mg/day in early pregnancy to a substantial 7.5 mg/day in late pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…A very interesting aspect of the research is reexamining the placenta as a unique player in the iron transfer from the pregnant female to fetuses. This issue of placental iron transport is being raised in an increasing number of studies, yet most have been in mice and may not include differences in the architecture of the mouse and pig placentae [19,79].…”
Section: Discussionmentioning
confidence: 99%